The Effect of Group Investigation Model Assisted by Diorama Media on Learning Outcomes in Science Material for Class V Students at SDN Pelemkerep 1 - Arrasyad, Muhammad Labib; Sutriyani, Wulan; Efendi, Abdullah (Lembaga Penelitian dan Pendidikan Mandala, 2024)
The appearance of progress in a country is that there is a good quality of education. There is a subject that is important in the advancement of science and technology and a person's character, the subject is IPAS. The research was conducted in order to determine the effect of Group Investigation Model assisted by Diorama Media. By doing learning in groups, it has the potential to increase student activity and learning outcomes in IPAS learning. This study uses a type of quantitative research in the form of a true experiment with the type of post-test only control group, which in its design has two classes, namely the control class and the experimental class. The samples used were class A with a total of 17 students and class B with a total of 15 students, sampling using random sampling techniques. The data collection technique used is a test method with a description format. The research results showed that learning using the Group Investigation Model with the help of Diorama Media in the experimental class could affect the improvement of learning outcomes.